Amino-containing modified silicon dioxide, biphenyl compound curing agent composition and application thereof, epoxy resin composition and epoxy resin product
By using amino-modified silica and biphenyl compound curing agent composition in epoxy resin for bonding reaction, the problems of permeability and compressive strength of epoxy resin products in petroleum fracturing field are solved, and the problem of permeability and compressive strength of epoxy resin products in the field of petroleum fracturing is achieved. The stability and compressive strength of the channel structure at high temperatures are improved.
Patent Information
- Application Number
- CN202311773024.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-12-21
AI Technical Summary
Existing epoxy resin products cannot have high permeability and compressive strength in the field of petroleum fracturing, and the pore structure is prone to collapse at high temperatures, affecting the permeability and stability.
The bonding reaction is carried out with the epoxy resin using the amino-containing modified silica and biphenyl compound curing agent composition, and the dendritic polyamino groups of the modified nano-silica react with the epoxy groups in the epoxy resin. , and use it in conjunction with reinforcement of specific structures to improve compressive strength and stability of the pore structure.
It realizes that epoxy resin products are not easily deformed at high temperatures, improves compressive strength and application stability, and is suitable for long-term formation operations.
Smart Images

Figure CN119264380A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic polymers, and in particular to an amino-modified silicon dioxide-biphenyl compound curing agent composition and application thereof, an epoxy resin composition and an epoxy resin product. Background Art
[0002] Epoxy resins are widely used in energy, machinery, chemical industry and other fields. At present, curing agents are generally added to synthesize epoxy resins to improve the performance of epoxy resins. Ethylenediamine is commonly used as a curing agent, but ethylenediamine is highly toxic when used for curing epoxy resins, and its application conditions are limited, and it is not suitable for water systems.
[0003] In addition, the epoxy resin prepared by the commonly used curing agent has low mechanical strength. When used as a proppant in the oil field, it cannot fill various small cracks in the formation well, and cannot guarantee a high permeability, nor can it adapt to special formation conditions and maintain a long working time.
[0004] Therefore, it is urgent to develop a product that can withstand high temperature and high pressure without affecting the permeability. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem that epoxy resin products in the prior art cannot be effectively used as proppants in the field of oil fracturing, which is specifically manifested in that they cannot have high permeability and compressive strength at the same time. At the same time, at high temperatures, the pore structure of the epoxy product is prone to collapse, causing the product to be easily deformed, affecting the permeability, and cannot be used for long-term and stable formation operations. Provided are an amino-modified silica, biphenyl compound curing agent composition and application, an epoxy resin composition and an epoxy resin product. The curing agent composition contains modified nano-silica with a specific structure and a reinforcing agent with a specific structure, so that the composition is added to the epoxy resin and can undergo a bonding reaction with the epoxy group in the epoxy resin, giving full play to the advantages of the two. At the same time, due to the presence of the reinforcing agent with a specific structure, the cured epoxy resin product has a greater compressive strength, and the pore structure of the epoxy resin product is not easy to collapse at high temperatures.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a curing agent composition, characterized in that the curing agent composition comprises a curing agent, a reinforcing agent and water;
[0007] The curing agent is modified nano-silicon dioxide shown in formula I;
[0008]
[0009] In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms;
[0010] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;
[0011] A is a structural unit derived from anhydride compounds, and B is a structural unit derived from polyamino compounds;
[0012] The enhancer has a structure shown in Formula II:
[0013] Having the structure shown in formula II;
[0014]
[0015] R3 and R4 are each independently selected from NH2, COOH or OH;
[0016] L is an integer of 0-10, and R5 is methylene or phenyl.
[0017] The second aspect of the present invention provides use of the curing agent composition described in the first aspect of the present invention as a curing agent in epoxy resin.
[0018] A third aspect of the present invention provides an epoxy resin composition, wherein the epoxy resin composition comprises an epoxy resin component and a curing agent component;
[0019] The curing agent component is the curing agent composition described in the first aspect of the present invention;
[0020] Wherein, the epoxy resin component and the curing agent component exist independently of each other.
[0021] A fourth aspect of the present invention provides an epoxy resin product, wherein the epoxy resin product is obtained by mixing and curing the epoxy resin composition described in the third aspect.
[0022] Through the above technical scheme, the amino-modified silica, biphenyl compound curing agent composition and application, epoxy resin composition and epoxy resin product provided by the present invention obtain the following beneficial effects: the polyamino groups in the modified silica present a dendritic morphology on the surface of the nano-silica, and when the modified nano-silica is added to the epoxy resin, the polyamino groups on its surface can react with the epoxy groups in the epoxy resin to give full play to the advantages of both, and at the same time, when used in combination with a reinforcing agent with a specific structure, the cured epoxy resin has a greater compressive strength when used as a proppant, and at the same time, its pore structure is not easy to collapse at high temperature, thereby improving its application stability. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The first aspect of the present invention provides a curing agent composition, characterized in that the curing agent composition comprises a curing agent, a reinforcing agent and water;
[0025] The curing agent is modified nano-silicon dioxide shown in formula I;
[0026]
[0027] In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms;
[0028] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;
[0029] A is a structural unit derived from anhydride compounds, and B is a structural unit derived from polyamino compounds;
[0030] The enhancer has a structure shown in Formula II:
[0031] Having the structure shown in formula II;
[0032]
[0033] R3 and R4 are each independently selected from NH2, COOH or OH;
[0034] L is an integer of 0-10, and R5 is methylene or phenyl.
[0035] In the present invention, the polyamino groups on the surface of the modified nano-silica present a dendritic morphology, and can react with the epoxy groups in the epoxy resin when applied to the epoxy resin, giving full play to the advantages between the two. At the same time, when used in combination with a reinforcing agent with a specific structure, the cured epoxy resin has a greater compressive strength when used as a proppant, and its pore structure is not easy to collapse at high temperatures.
[0036] According to the present invention, in Formula I, the acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride.
[0037] According to the present invention, the polyamino compound has a linear polyethylene polyamino compound or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000, which is represented by formula III:
[0038]
[0039] Here, p is an integer from 1 to 6.
[0040] In the present invention, the polyamino compound is selected from the above compounds, so that the amino content in the modified nano-silicon dioxide is high, and the curing performance of epoxy resin is further improved.
[0041] According to the present invention, the particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g.
[0042] According to the present invention, the particle size of the modified nano-silicon dioxide is 10-500nm, and the specific surface area is 50-500m 2 / g.
[0043] According to the present invention, the particle size dispersion coefficient of the modified nano-silicon dioxide is 0.09-0.15.
[0044] According to the present invention, the amino content of the modified nano-silicon dioxide is 0.1-5 mmol / g.
[0045] In the present invention, the modified nano-silicon dioxide can be prepared according to the following steps:
[0046] S1. In the presence of a protective gas, dispersing nano-silica particles M in a first solvent, adding aminosilane to carry out a first reaction, and obtaining amino-functionalized nano-silica of formula IV;
[0047]
[0048] S2. In the presence of a second solvent, subjecting the amino-functionalized nano-silica to a second reaction with an acid anhydride compound to obtain a carboxyl-functionalized nano-silica of formula V;
[0049]
[0050] S3. In the presence of an alkaline catalyst, the carboxyl-functionalized nano-silica is mixed with a condensation agent, activated, and then a polyamino compound is added to carry out a third reaction to obtain modified nano-silica.
[0051] In the present invention, the protective gas is nitrogen and / or an inert gas.
[0052] In the present invention, steps S1, S2 and S3 each independently comprise separation, washing and drying steps.
[0053] Furthermore, there is no particular limitation on the separation method, and for example, it may be at least one of filtration, rotary evaporation or centrifugal separation.
[0054] Furthermore, there is no particular limitation on the washing conditions. For example, the washing can be performed 3-4 times using conventional solvents in the art, wherein the solvent can be at least one of methanol, ethanol, and acetone. Preferably, in step S1, acetone and dichloromethane are used for washing.
[0055] According to the present invention, in step S1, the mass ratio of the nano-silica particles M to the aminosilane is 5-100:1.
[0056] Furthermore, the mass ratio of the nano-silica particles M to the aminosilane is 10-50:1.
[0057] According to the present invention, the aminosilane is at least one selected from aminopropyltriethoxysilane, aminopropyltrimethoxysilane, aminopropylmethyldimethoxysilane and aminopropylmethyldiethoxysilane.
[0058] According to the present invention, the conditions of the first reaction include: reaction temperature of 120-160° C., and reaction time of 2-24 h.
[0059] Furthermore, the conditions of the first reaction include: reaction temperature of 120-140° C., and reaction time of 8-16 h.
[0060] According to the present invention, in step S2, the mass ratio of the amino-functionalized nano-silica to the acid anhydride compound is 5-100:1.
[0061] Furthermore, the mass ratio of the amino-functionalized nano-silica to the acid anhydride compound is 10-50:1.
[0062] According to the present invention, the acid anhydride compound is at least one selected from maleic anhydride, phthalic anhydride and succinic anhydride.
[0063] According to the present invention, the conditions of the second reaction include: reaction temperature of 90-160° C., and reaction time of 2-12 h.
[0064] Furthermore, the conditions of the second reaction include: reaction temperature of 90-120° C., and reaction time of 6-12 h.
[0065] According to the present invention, the first solvent and the second solvent are each independently selected from at least one of toluene, xylene, benzene and N,N-dimethylformamide.
[0066] According to the present invention, in step S3, the mass ratio of the carboxyl-functionalized nano-silica, the condensation agent, the alkaline catalyst and the polyamino compound is 1:0.05-0.5:0.01-0.1:0.1-5.
[0067] In the present invention, when the mass ratio of the carboxyl-functionalized nano-silica, the condensing agent, the alkaline catalyst and the polyamino compound meets the above preferred range, the obtained modified nano-silica has the best comprehensive performance and further improves the curing performance of epoxy resin.
[0068] Furthermore, the mass ratio of the carboxyl-functionalized nano-silica, the condensation agent, the alkaline catalyst and the polyamino compound is 1:0.05-0.3:0.01-0.05:0.1-4.
[0069] According to the present invention, the condensing agent is selected from one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
[0070] According to the present invention, the base catalyst is selected from at least one of 4-dimethylaminopyridine, 1,8-diazabicycloundec-7-ene and triethylamine.
[0071] According to the present invention, the conditions of the third reaction include: reaction temperature of 0-40°C, reaction time of 2-48h.
[0072] Furthermore, the conditions of the third reaction include: reaction temperature of 10-25° C., and reaction time of 8-16 h.
[0073] According to the present invention, in step S3, the activation conditions include: activation temperature of 10-25° C., and activation time of 8-24 h.
[0074] According to the present invention, in formula II, R3 and R4 are each independently selected from NH2 or COOH.
[0075] According to the present invention, L is an integer of 0-4, and R5 is a methylene group.
[0076] According to the present invention, the reinforcing agent is selected from at least one of 4,4'-methylenedianiline and / or 3,3',5,5'-tetramethylbenzidine. In the present invention, the inventors have found that the reinforcing agent selected from the above types can further improve the high temperature resistance of the cured epoxy resin product.
[0077] According to the present invention, based on the total weight of the curing agent composition, the content of the curing agent is 40-60wt%, the content of the reinforcing agent is 5-10wt%, and the content of the water is 30-55wt%.
[0078] In the present invention, the components in the curing agent composition meet the above ranges, and the components synergize with each other, so that when the composition is applied to epoxy resin, the compressive strength of the epoxy resin after curing is further improved, and the epoxy resin product after curing is not easy to deform at high temperature.
[0079] Furthermore, based on the total weight of the curing agent composition, the content of the curing agent is 50-60wt%, the content of the reinforcing agent is 6-8wt%, and the content of the water is 32-44wt%.
[0080] According to the present invention, the curing agent composition further comprises 2-5 parts by weight, preferably 3-4 parts by weight of an accelerator.
[0081] According to the present invention, the accelerator is selected from polycarboxylic acids and / or small molecule polyamines.
[0082] According to the present invention, the polycarboxylic acid is selected from at least one of terephthalic acid, citric acid, tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid.
[0083] According to the present invention, the small molecule polyamine is at least one selected from polyethylene polyamine, ethylenediamine, 1,6-hexanediamine, isophoronediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, hydrazine and dihydrazide.
[0084] According to the present invention, the accelerator is a mixture of polycarboxylic acid and small molecule polyamine, wherein the mass ratio of the polycarboxylic acid to the small molecule polyamine is 1:0.1-0.8.
[0085] In the present invention, the accelerator is a mixture of polycarboxylic acid and small molecule polyamine, which can improve the high temperature resistance of the curing agent composition while ensuring its fluidity. Further, when the mass ratio of the polycarboxylic acid to the small molecule polyamine meets the above range, the high temperature resistance of the curing composition can be significantly improved, and it is not easy to deform at high temperature.
[0086] Furthermore, the mass ratio of the polycarboxylic acid to the small molecule polyamine is 1:0.4-0.6.
[0087] According to the present invention, the curing agent composition further comprises 0.01-0.06 parts by weight of a co-curing agent.
[0088] Furthermore, the auxiliary curing agent is selected from at least one of zirconium oxychloride, aluminum trichloride, titanium tetrachloride and ferric chloride.
[0089] According to the present invention, at 25° C., the apparent viscosity of the curing agent composition is 100-500 mPa·s, preferably 200-300 mPa·s.
[0090] The second aspect of the present invention provides a use of the curing agent composition described in the first aspect of the present invention as a curing agent in epoxy resin.
[0091] A third aspect of the present invention provides an epoxy resin composition, wherein the epoxy resin composition comprises an epoxy resin component and a curing agent component;
[0092] The curing agent component is the curing agent composition described in the first aspect of the present invention;
[0093] Wherein, the epoxy resin component and the curing agent component exist independently of each other.
[0094] In the present invention, in the epoxy resin composition, the epoxy resin and the curing agent are stored separately and independently, which can prevent the epoxy resin from curing in advance and affecting the subsequent normal use. When used in the subsequent process, the epoxy resin and the curing agent are injected into the formation at the same time, so that they undergo a curing reaction under the formation, and the honeycomb product is used as a proppant, which can ensure high permeability while having high compressive strength.
[0095] In the present invention, the curing agent component may also include conventional auxiliary agents in the art, such as emulsifiers, etc. There are no special requirements for the specific type and amount of the emulsifier. Conventional types of emulsifiers in the art can be used and added according to conventional amounts in the art.
[0096] According to the present invention, the amount of the curing agent component is 30-80 parts by weight relative to 100 parts by weight of the epoxy resin component.
[0097] In the present invention, the amount of the curing agent used satisfies the above range, so that the cured epoxy resin has a higher compressive strength and is not easily deformed at high temperatures.
[0098] Furthermore, relative to 100 parts by weight of the epoxy resin, the amount of the curing agent component is 40-60 parts by weight.
[0099] A fourth aspect of the present invention provides an epoxy resin product, which is obtained by mixing and curing the epoxy resin composition described in the third aspect of the present invention.
[0100] According to the present invention, at 90° C. and 40 MPa, the deformation rate of the epoxy resin product is less than or equal to 5%, preferably less than or equal to 3%, and more preferably less than or equal to 1%.
[0101] According to the present invention, the softening point of the epoxy resin product is 90-120°C, preferably 110-120°C.
[0102] The present invention will be described in detail below by way of examples. In the following examples,
[0103] The particle size of modified nano-silica was measured by transmission electron microscopy (TEM) and scanning electron microscopy (SEM);
[0104] The specific surface area of modified nano-silica was measured by BET adsorption method;
[0105] The particle size dispersion coefficient (PDI) of modified nano-silica was measured by laser particle size analyzer (DLS) method;
[0106] The amino content in modified nano-silica was measured by acid-base neutralization titration method;
[0107] The apparent viscosity of the curing agent composition was measured by a six-speed rotational viscometer method;
[0108] The deformation rate of epoxy resin products is measured according to the following method:
[0109] At normal pressure and 25°C, the diameter of the tested honeycomb resin product is D0. At 40MPa and 90°C, the honeycomb resin product is extruded using a high and low temperature universal material testing machine. The diameter of the tested honeycomb resin product after extrusion is D1. The deformation rate = (D0-D1) / D0×100%.
[0110] Preparation of Nano-Silica M1
[0111] S1. Preparation of aminopropyl functionalized nano-silica:
[0112] Weigh 2g of the average particle size of 30nm and the specific surface area of 200m 2 / g of nano-silica particles were dispersed in 100mL of anhydrous toluene, and then 0.2g of aminopropyltriethoxysilane was added. The mixture was refluxed and stirred at 150°C for 24 hours under nitrogen protection. After the reaction, the solid product was centrifuged to obtain the solid product. The solid product was repeatedly washed with acetone and dichloromethane for 3 times, and vacuum dried at 40°C for 12 hours to obtain aminopropyl-functionalized nano-silica.
[0113] S2. Preparation of carboxyl functionalized nano-silica:
[0114] Weigh 2 g of the aminopropyl-functionalized nano-silica prepared above, disperse it in 50 mL of xylene, add 0.2 g of maleic anhydride, reflux and stir at 160 ° C for 6 hours under nitrogen protection, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40 ° C for 12 hours to obtain carboxyl-functionalized nano-silica.
[0115] S3. Preparation of modified nano-silica:
[0116] Weigh 1 g of the carboxyl-functionalized nano-silica prepared above, disperse it in 50 mL of toluene, add 0.25 g of diisopropylcarbodiimide (DIC) and 0.06 g of 1,8-diazabicycloundec-7-ene (DBU), stir and activate at room temperature (25°C) for 1 hour, then add 4 g of polyethyleneimine (number average molecular weight of 1500), continue to react at room temperature for 12 hours, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40°C for 12 hours to obtain modified nano-silica M1 with formula I structure, wherein n is 0, m is 3, and x is 3.
[0117] The particle size of the modified nano-silicon dioxide M1 is 30 nm and the specific surface area is 300 m 2 / g, the amino content is 2mmol / g, and the dispersion coefficient PDI is 0.11.
[0118] Preparation of Nano-Silica M2
[0119] The preparation method of M1 was followed, except that the specific surface area of the nano-silica particles was 100 m 2 / g, and in step S3, the amount of polyethyleneimine used is 0.4g; the particle size of the modified nano-silicon dioxide M2 is 30nm, and the specific surface area is 230m 2 / g, the amino content is 0.1mmol / g, and the dispersion coefficient PDI is 0.13.
[0120] The following preparation examples and comparative preparation examples are used to illustrate the preparation of the curable resin composition.
[0121] Preparation Example 1
[0122] 55 g of modified nano-silica M1, 8 g of 4,4'-methylenedianiline (DDM1), 2.2 g of terephthalic acid, 0.9 g of polyethylene polyamine, 0.04 g of zirconium oxychloride, and 49.8 g of water were mixed and stirred uniformly to obtain a curing agent composition A1, and its apparent viscosity was tested to be 198 mPa·s.
[0123] Preparation Example 2-10
[0124] Curing agent compositions A2-A10 were prepared according to the method of Preparation Example 1, except that the types and amounts of curing agent, accelerator, and enhancer were different from those in Preparation Example 1, as shown in Table 1 and Table 1 (Continued). The apparent viscosities of curing agent compositions A2-A10 are shown in Table 1 and Table 1 (Continued).
[0125] Table 1
[0126]
[0127] * Refers to the mass ratio of the amount of accelerator 1 to the amount of accelerator 2
[0128] Table 1 (continued)
[0129]
[0130]
[0131] Comparative Preparation Examples D1-D3
[0132] Curing agent compositions D1-D3 were prepared according to the method of Preparation Example 1, except that the types and amounts of curing agent, accelerator and enhancer were different from those in Preparation Example 1, as shown in Table 2. The apparent viscosities of curing agent compositions D1-D3 are shown in Table 2.
[0133] Table 2
[0134]
[0135] The following examples are used to illustrate the preparation of epoxy resin products.
[0136] Examples 1-10
[0137] 65 g of the curing agent composition prepared in Preparation Examples 1-10 was mixed with 100 g of epoxy resin E44 and cured at a curing temperature of 120° C. for 4 h to obtain epoxy resin products P1-P10. The deformation rate and softening point of the products were tested at 90° C. and 40 MPa, and the results are shown in Table 3.
[0138] Comparative Examples 1-3
[0139] 65 g of the curing agent composition obtained in Comparative Preparation Examples 1-3 was mixed and cured with 100 g of epoxy resin E44 at a curing temperature of 120° C. for 4 h to obtain epoxy resin products DP1-DP3. The deformation rate and softening point thereof were tested at 90° C. and 40 MPa. The results are shown in Table 3.
[0140] Table 3
[0141]
[0142]
[0143] It can be seen from the results in Table 1 that embodiments 1-10 of the present invention achieve good technical effects, wherein the deformation rate at 90°C and 40 MPa is not higher than 4%, and the softening point is not lower than 90°C.
[0144] Furthermore, preferred embodiments 1-3 achieve significantly better effects, specifically, the deformation rate at 90°C and 40 MPa is not higher than 2.6%, while the softening point is not lower than 110°C.
[0145] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A curing agent composition, characterized in that The curing agent composition comprises a curing agent, a reinforcing agent and water; The curing agent is modified nano-silicon dioxide shown in formula I; In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms; n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3; A is a structural unit derived from anhydride compounds, and B is a structural unit derived from polyamino compounds; The enhancer has a structure shown in Formula II: Having the structure shown in formula II; R3 and R4 are each independently selected from NH2, COOH or OH; L is an integer of 0-10, and R5 is methylene or phenyl.
2. The curing agent composition according to claim 1, wherein In Formula I, the acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride; Preferably, the polyamino compound has a linear polyethylene polyamino compound having a structure shown in Formula III or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000: Here, p is an integer from 1 to 6.
3. The curing agent composition according to claim 1 or 2, wherein The particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g; Preferably, the particle size of the modified nano-silicon dioxide is 10-500nm and the specific surface area is 50-500m 2 / g; Preferably, the particle size dispersion coefficient of the modified nano-silicon dioxide is 0.09-0.15; Preferably, the amino content of the modified nano-silica is 0.1-5 mmol / g.
4. The curing agent composition according to any one of claims 1 to 3, wherein In formula II, R3 and R4 are each independently selected from NH2 or COOH; Preferably, L is an integer of 0-4, and R5 is a methylene group.
5. The curing agent composition according to any one of claims 1 to 4, wherein The enhancer is selected from 4,4'-methylenedianiline and / or 3,3',5,5'-tetramethylbenzidine.
6. The curing agent composition according to any one of claims 1 to 5, wherein Based on the total weight of the curing agent composition, the content of the curing agent is 40-60 parts by weight, the content of the reinforcing agent is 5-10 parts by weight, and the content of the water is 30-55 parts by weight; Preferably, based on the total weight of the curing agent composition, the content of the curing agent is 50-60 parts by weight, the content of the biphenyl is 6-8 parts by weight, and the content of the water is 32-44 parts by weight.
7. The curing agent composition according to any one of claims 1 to 6, wherein The curing agent composition further comprises 2-5 parts by weight, preferably 3-4 parts by weight of an accelerator; Preferably, the accelerator is selected from polycarboxylic acids and / or small molecule polyamines; Preferably, the polycarboxylic acid is at least one selected from terephthalic acid, citric acid, tartaric acid, oxalic acid, malic acid, citric acid, and ascorbic acid; Preferably, the small molecule polyamine is selected from at least one of polyethylene polyamine, ethylenediamine, 1,6-hexanediamine, isophoronediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, hydrazine and bishydrazide.
8. The curing agent composition according to claim 7, wherein The accelerator is a mixture of polycarboxylic acid and small molecule polyamine, wherein the mass ratio of the polycarboxylic acid to the small molecule polyamine is 1:0.1-0.8, preferably 1:0.4-0.
6.
9. The curing agent composition according to any one of claims 1 to 8, wherein The curing agent composition further comprises 0.01-0.06 parts by weight of a co-curing agent; Preferably, the auxiliary curing agent is selected from at least one of zirconium oxychloride, aluminum trichloride, titanium tetrachloride and ferric chloride.
10. The curing agent composition according to any one of claims 1 to 9, wherein At 25° C., the apparent viscosity of the curing agent composition is 100-500 mPa·s, preferably 200-300 mPa·s.
11. Use of the curing agent composition according to any one of claims 1 to 9 as a curing agent in epoxy resin.
12. An epoxy resin composition, characterized in that The epoxy resin composition comprises a resin component and a curing agent component; The curing agent component is the curing agent composition according to any one of claims 1 to 9; Wherein, the epoxy resin component and the curing agent component exist independently of each other.
13. The epoxy resin composition according to claim 12, wherein Relative to 100 parts by weight of epoxy resin, the amount of the curing agent component is 30-80 parts by weight, preferably 40-60 parts by weight.
14. An epoxy resin product, characterized in that: The epoxy resin product is obtained by mixing and curing the epoxy resin composition according to claim 12 or 13.
15. The epoxy resin product according to claim 14, wherein: At 90°C and 40MPa, the deformation rate of the epoxy resin product is less than or equal to 5%, preferably less than or equal to 3%, and more preferably less than or equal to 2%; Preferably, the softening point of the epoxy resin product is 90-120°C, preferably 110-120°C.
Citation Information
Patent Citations
Modified nanometer silicon dioxide filling epoxy resin composition as well as preparation method and product thereof
CN103408904A
Toughened and enhanced epoxy resin composition
CN108892929A
Bi-component thermosetting epoxy resin composition and application thereof, bi-component thermosetting epoxy resin and preparation method and application thereof
CN114316869A
Epoxy resin composition, preparation method and application thereof, LED display screen, packaging method of LED display screen and electronic product
CN116063818A
Heat-curable epoxy resin composition with high storage stability
EP3476882A1